Draw a circle and show sin & cos axes on it and relevant angles...then all will be clear.
I was reading through a text book on trigometric identities and gave the definition:
- cos(a) = sin(a + 90) // (1a)
- sin(a) = cos(a - 90) // (2a)
then it went to derive another two new identities from the above identities
- cos(a) = -sin(a-90) // (1b)
- sin(a) = -cos(a+90) // (2b)
What I don't understand is steps involved from deriving (1a) to (1b) and (2a) to (2b), any help would be appreciated
Thank you for your reply, although specifically I wanted to see how you could derive the identities algebraically. That is, cos(a) = sin(a + 90) to cos(a) = -sin(a-90) and similalrly for the other identity. If you could show the steps, that would be great